Agile Productivity Unleashed - JAMIE LYNN COOKE (IT Governance Publishing, 2014)
Companies are constantly in search of better ways to run their businesses, maintain customer loyalty, and increase their competitive advantage. For over twenty years, Agile practices and techniques have addressed this demand by providing companies such as Yahoo!, Google, Nokia Siemens Networks and Microsoft with more efficient processes, higher quality outputs and greater customer satisfaction. It appears, however, that companies outside of the information technology and manufacturing sectors are generally unfamiliar with Agile approaches – and those that are familiar with Agile tend to see it as restricted to only these sectors. (This is largely due to the fact that proponents of Agile approaches tend to come from more technical backgrounds – and information regarding these approaches has generally been presented only in a technical context.) Agile Productivity Unleashed: Proven approaches for achieving real productivity gains in any organization introduces the general business community to the Agile practices and techniques that have dramatically improved the information technology, product development and manufacturing sectors over the past three decades – and demonstrates how the key principles that underpin Agile approaches can be used to significantly increase productivity, quality and customer satisfaction in every industry sector. Agile Productivity Unleashed helps businesses to understand why upfront detailed planning is destined to fail, why teams are significantly more productive when they control their own outcomes, and why market testing provides a false sense of security. It introduces the general business community to powerful Agile techniques, such as responsive planning, direct stakeholder engagement, management by self-motivation, ‘just-in-time communication’ and immediate status tracking. Agile Productivity Unleashed challenges the reader to reconsider their ‘business as usual’ activities in favor of more responsive, collaborative and customer-driven approaches. Most importantly, Agile Productivity Unleashed describes Agile principles and approaches in terms that really make sense to business professionals. We are at the forefront of the evolution of Agile approaches, from technology- and sector-specific practices to general business applicability. Agile Productivity Unleashed is designed to show the business community the latent potential in Agile approaches, and inspire readers to take the first step in introducing Agile benefits in their organizations.